Bioenergy and agriculture: Promises and challenges - Hazell, Peter B. R.; Pachauri, R. K. (International Food Policy Research Institute, 2006)
This set of policy briefs examines the potential opportunities and risks bioenergy may pose for poor people and farmers in developing countries. The briefs consider economic, social, environmental, and science and technology issues. They look at how increased bioenergy production may affect the global food balance and examine the need for further research and development in the bioenergy field.